Study of Anti-Inflammatory Effects of Black Cumin (Nigella Sativa) and Honey on Mice (Mus Musculus) - Zahoor, Tayyaba; Ali, Iftikhar; Naureen, Irum (Journal of Zoological Research, 2023)
The study was conducted to determine the effect of Nigella sativa (Kalonji) and Honey as an anti-inflammatory agent for humans and animals. The study was carried out on 20 Albino Mice of almost equal size and weight. All the mice were given 5% solution of formalin in a dose of 0.5ml injection in their right hind paw to produce artificial inflammation. The mice were divided into four groups of five animals in each and were randomly allotted to four treatments as Group A (Control) where no Nigella sativa extract and honey were given, Group B where the mice were given only the ethanolic extract of Nigella sativa in the dose of 0.05ml injection as a remedy of inflammation, Group C where the mice were given only the honey orally in a dose of 0.05mg and Group D where mice were given 50% (0.025ml) intraperitoneally of Nigella sativaextract and 50% (0.75mg) of honey as an anti-inflammatory agents. The data was statistically analyzed by the Analysis of Variance (ANOVA) and the results showed that the inflammation was significantly (p<0.05) reduced in mice given treatments compared to untreated control group and among treated groups. The mice given the extract of Nigella sativa (Group B) showed better results (p<0.05) in reducing the inflammation compared to other groups (C and D), Group D where the mice were given 50% (0.025ml) Nigella sativa extract and 50% (0.75mg) honey showed better results (p<0.05) than mice given only honey. Overall, both the extract of Nigellasativa and the honey were almost equally successful in reducing the inflammation in mice which showed that these two agents can successfully be used as anti-inflammatory drugs in humans and animals.
Keywords: Nigella sativa; Honey; Albino mice; formalin; ethanol extract; inflammation.